Effect of Weight on Outcomes of Children Undergoing Hematopoietic Cell Transplantation. (14th February 2013) - Myers, Laura C.; Sun, Pengling; Brennan, Lisa L.; London, Wendy B.; Guinan, Eva C.
<x xml:space="preserve">Abstract</x> Chemotherapy dosing in hematopoietic cell therapy (HCT) conditioning regimens is based on patient weight. We hypothesized that potential underdosing or overdosing of patients with significant deviation of weight from normal might alter HCT outcomes, such as early mortality, overall or organ-specific toxicity, and/or relapse. We therefore conducted a retrospective analysis of 400 children between the ages of 2 and 18 years who underwent HCT for malignant or nonmalignant disease at Boston Children's Hospital over a 10-year period. Using the Centers for Disease Control and Prevention standard weight classification schema, we found no evidence to suggest a difference in survival or in time to engraftment or in relapse in patients with malignant disease. In the subgroups of patients either receiving autologous HCT or with underlying malignancy, combined overweight and obese patients had a higher rate of any organ, but not organ-specific, Grade 3–5 toxicity compared with the normal weight group. The study was not powered to detect a difference between underweight and normal weight patients. These data suggest that multiple outcome measures over the first year after HCT are unaffected by weight.